Mengapa Late Childhood Merokok? - Taryaka, Apriyani; Hurriyati, Evi Afifah (Humaniora, 2011)
This research is set to determine the cause of late childhood smoking and whether the factor behind late child hood smoking is the same with teenagers. The background of this research are the findings of Tobacco Control Support Center that 3 out of 10 students are found to be smoking before reaching the age of 10. This research uses qualitative case study research through observation and in-depth direct interview towards 3 male subjects aged 11 who smokes every day. Results show that the 3 subjects smoke due to personal factor, friends, family and cigarette advertisements. Most of the factor behind the smoking behavior are found to be in the sociogenic motive category. Therefore, it could be concluded that the smoking behavior of the 3 subjects is not purely from the personal factor, but more of the environmental factor having big part in creating smoking behavior in the 3 subjects. Factors behind smoking behavior of the three late childhood subjects and teenagers have a lot in common. Friend factor is the first driving factor of smoking behavior on both late childhood and teenager.